Does Speed Matter? The Association Between Case Processing Time in Juvenile Court and Rearrest - Novak, Abigail (Criminal justice policy review, 2022)
The present study assessed the relationship between case processing time and rearrest among a sample of first-time juvenile offenders referred to the Florida juvenile justice system and examined the extent to which this association varied by youth and case characteristics. Propensity score analyses suggested youth with longer case processing times had higher odds of being rearrested within 1 year compared to youth with shorter case processing times. Subgroup analyses suggested differences in the effects of case processing time by youth and case-level characteristics. According to results, policymakers should prioritize implementing and enforcing case processing time restrictions in their jurisdictions, particularly for detained youth and remain aware of the potential ensnaring implications of longer case processing times to reduce rearrest rates for first-time juvenile offenders.